Habitat and Behavioral Observation of Indian Flying Fox Pteropus giganteus (BRÜNNICH, 1782) in Sallaghari, Bhaktapur, Nepal - Prajapati, Jamuna; Chalise, Mukesh Kumar; Karmacharya, Dikpal Krishna (Journal of Natural History Museum, 2020)
The study on Indian flying fox (Pteropus giganteus), the most diverse group of mammals, was conducted from17th September, 2016 to 3rd March, 2017 at Sallaghari, Bhaktapur to collect baseline information on habitat, behavior, population and threats. The population structure and estimated populations along with their habitat using direct observation and the branch estimation method were assessed. The general behaviour of the individual animal was observed and recorded using focal animal sampling over a 10 minute periods either in the morning or evening. Local people and members of the Nepal Army were interviewed using semi-structured questionnaires in order to assess threats. Most flyng fox were found roosting in tall Eucalyptus spp. trees and the highly branched Populus spp. Resting was observed as the most the dominant behavior among male, female and young individuals during the study period. Highest populations (n=1421) were observed in September 2016 and lowest (n=36) in February 2017. Habitat destruction, lack of food, urbanization and electrocution were the major threats to P. giganteus. The population is decreasing compared to previous studies. Electrocution and persecution by humans are the major causes of accidental death each year. Therefore, in order to conserve and save this species, habitat and afforestation along with awareness programs should be implemented urgently.